Comments on PDIV testing procedure according to IEC 61294 - Pattanadech, Norasage; Muhr, Michael (My University, 2017)
—In this paper, partial discharge inception voltage (PDIV) and partial discharge (PD) activity of mineral oil with water content of 4 ppm are investigated. The PDIV test procedure was performed according to IEC 61294. Then, the PDactivitywas recorded for 1 minute at 1.1 PDIV level. The investigation wasconducted with a needle – plane electrode and a needle –sphere electrode by which different tip radius needles, plane electrodes, and various diameter sphere electrodes were used for the experiments. The PDIV and PD activity test results are reported in this paper. It was found that PDIV strongly depends on the electrode configuration and the gap distance. From the experiments,PDIV values of some electrode systems were not obtained due to the problems of breakdown events occurring during the experiments.Theparticular patterns for PDIV testing to explain the possibility PD and breakdown events which may occur during PDIV testing in accordance with IEC 61294 are developed. The particular patterns for PDIV testingare divided into four cases as the followings: The first PD pulse coexisting with PDIV, the low risk of breakdown for PDIV experiment, the medium risk of breakdown for PDIV experiment and the high risk of breakdown for PDIV experiment. In case of the very simple case PDIV and the lower risk of breakdown for PDIV experiment, the PDIV can be detected without breakdown occur. However, in the case of the medium risk of breakdown for PDIV experiment breakdown may take place before or after the PDIV is detected. In the case of high risk of breakdown for PDIV measurement, breakdown takes place easily during performing the PDIV experiment.Therefore, the exact PDIV valuesare not be obtained for such cases. To avoid the breakdown events which may occur during PDIV experimentaccording to IEC 61294 was performed, the combined PDIV measurement was recommended. Besides, PDIV testing with the combined PDIV method provided the lower PDIVwhich was closer to the theoretical PDIV compared with testing in accordance with IEC61294.
Keywords: Mineral oil; Partial discharage inception voltage; Partial discharge; Patial discharge inception voltage testing standard